Pewarisan Sifat Warna Bunga, ukuran Polongan dan Bobot Polong pada persilangan Buncis )Phaseolus vulgaris L.) Kultivar Rich green dengan Kultivar FLO=Inheritance of Flower Colour, Pod Size and Pod Weight - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The research was done in three stages: (1). Establisment of Fj from crossing between Rich Green (PI) with FLO (P2) and its reciprocal crossing (Fu). (2). Establisment F2 from selfing of F,. BC11 was made from crossing between Fj with Pj and BC^ was made between crossing F, and P2. (3). Evaluation of P,, P2, F,, F]r,F2, BCn dan BC]2. The objective of research was to study the inheritance of flower colour, pod length, pod diameter and pod weight. Parameters observed were flower colour, pod length, pod diameter and pod weight. Result of the research showed that flower colour character was inherited qualitatively, it was controlled by 1 gene. F2 progeny segregated in a ratio of 3:1. Pod length character was inherited quantitatively , it was controlled by many genes. The heritability estimate of pod length character was categorized high and the expected genetic advance was rather high. There were interaction of aditive x dominant. Pod diameter character was inherited quantitatively, it was controlled by many genes. The heritability estimate of pod diameter character was categorized of medium and expected genetic advance was low. There were interaction of aditive x aditive, aditive x dominant and dominant x dominant. Pod weight character was inherited quantitatively, it was controlled by many genes. The heritability estimate of pod weight character was categorized of medium and the expected genetic advance was low. There were interaction of the aditive x aditive, aditive x dominant and dominant x dominant. There was no mathernal effect in inheritance of the flower colour, pod length, pod diameter and pod weight. The characters of flower colour, pod length, pod diameter and pod weight were controlled by the nuclear genes.